When do firms respond to external pressure for environmental management? Insights from deterrence theory - Listowel Owusu Appiah (Sustainable Futures)
Extant literature indicates that external stakeholder pressure drives corporate environmental management practices. However, in practice, firms operating within the same context often exhibit divergent responses to stakeholder ecological demands. This research integrates stakeholder theory and deterrence theory to explore how a firm's perception of the consequences of non-compliance—referred to as the 'level of deterrence'—moderates the relationship between external pressure and environmental management practices. By combining these theoretical perspectives, the study advances the understanding of why firms respond differently to similar stakeholder pressures. The conceptual framework is tested using survey data from 157 small-scale manufacturers in Ghana, a Sub-Saharan African country. Partial least squares structural equation modeling (PLS-SEM) and hierarchical ordinary least squares regression were employed to analyze the relationships among the variables. The results reveal that the influence of external pressure on environmental management is strengthened when deterrence is high and weakened when deterrence is low. These findings underscore the need to reassess the certainty, swiftness, and severity of penalties for environmental violations in developing economies while highlighting the importance of stakeholder influence in driving corporate sustainability efforts.